A Note on Descriptive Categories and Comparative Concepts in Linguistics - Willems, Klaas (Acta Universitatis Danubius. Communicatio, 2024)
This note takes issue with the claim that language-specific descriptive categories and crosslinguistic comparative concepts are different “kinds of things” (Haspelmath, 2018). Against the backdrop of Eugenio Coseriu’s epistemology of the language sciences it is argued that the general concepts used to make comparisons between languages are manifestations of potentially universal categories, which fall within the purview of linguistic intuition. In this sense, the relationship between categories of language and comparative concepts of linguistics reflects the creativity of language as enérgeia, which is a “synthetic a priori” in the Kantian sense.